Zhodnocení používání cash poolingu ve vybraném podniku - Mayerová, Hana (Vysoké učení technické v Brně. Fakulta podnikatelská, 2014)
Diplomová práce se zabývá zhodnocením výhod a nevýhod cash poolingu. Cílem diplomové práce je posoudit výhodnost používaných metod cash managementu a eventuelní vhodnost zapojení poboček zkoumané společnosti do cash poolingové struktury koncernu. Teoretická část se zabývá analýzou základních pojmů cash poolingu. Analytická část obsahuje představení společnosti. Návrhová část posuzuje vhodnost cash poolingu a možnost zavedení cash poolingu do ostatních poboček.

This diploma thesis deals with evaluation of the advantages and disadvantages of cash pooling. The aim of the thesis is to assess profitability of the cash management methods and eventual benefits of involvement of branches of surveyed company in the Group cash pooling. The theoretical part analyzes basic concepts of cash pooling, analytical part contains presentation of the company. Draft part assesses suitability of pooling cash and the feasibility of introducing cash pooling in other branches.
Appreciation of Cash Pooling in a Choosen Enterprise
Keywords: Cash management; cash pooling; reálný cash pooling; fiktivní cash pooling; netting; Cash management; cash pooling; real cash pooling; notional cash pooling; netting